Increase and regression of the protective effect of high altitude acclimatization on the isoprenaline-induced necrotic lesions in the rat myocardium - Faltová, E; Mráz, M; Pelouch, V; Procházka, J; Ostádal, B (Physiologia Bohemoslovaca, 1987)
Cardiac resistance to the cardiotoxic effect of isoprenaline--ISO (single dose of 0.1 mg X kg-1) was studied in rats acclimatized to intermittent high altitude--IHA (barochamber, 8 h a day, 5 days a week, stepwise up to 7000 m). The extent of lesions was evaluated quantitatively by means of the increased accumulation of 203HgCl2. Five weeks' acclimatization was followed by a marked increase in the resistance of the myocardium to the necrogenic effect of ISO; this effect was more expressed in the left ventricle, so that the right to left difference generally observed under normoxic conditions disappeared. The increased resistance of the myocardium to ISO-induced damage persisted long after the animals had been returned to normoxic conditions; even six weeks after the last hypoxic exposure the sensitivity of the myocardium to damage had still not returned to the values of unacclimatized animals.
Keywords: tuková tkáň; aklimatizace; velikost orgánu; přijímání potravy; léková rezistence; Eating; nekróza; Rats, Inbred Strains; krysa rodu Rattus; Acclimatization; Hypoxia; zvířata; hypoxie; Isoproterenol; Male; Altitude; Drug Resistance; Heart; Rats; myokard; Body Weight; Animals; Organ Size; tělesná hmotnost; mužské pohlaví; srdce; Myocardium; Necrosis; isoprenalin; Adipose Tissue; inbrední kmeny potkanů; nadmořská výška